Effectiveness of dupilumab treatment in 95 patients with atopic dermatitis: daily practice data. (16th October 2019) - de Wijs, L.E.M.; Bosma, A.L.; Erler, N.S.; Hollestein, L.M.; Gerbens, L.A.A.; Middelkamp‐Hup, M.A.; Kunkeler, A.C.M.; Nijsten, T.E.C.; Spuls, P.I.; Hijnen, D.J.
Summary: Background: Dupilumab is the first biologic registered for the treatment of moderate‐to‐severe atopic dermatitis (AD), and efficacy was shown in phase III clinical trials (primary outcome at week 16 was reached in 38% of patients). Currently, there are limited daily practice data available for dupilumab, especially when it is combined with systemic immunosuppressants. Objectives: To evaluate dupilumab treatment in daily practice in patients with AD. Methods: In this observational cohort study, we prospectively included all adult patients with AD who had been treated with dupilumab in two university hospitals in the Netherlands. Concomitant systemic immunosuppressive treatment was monitored. Physician‐reported outcome measures and patient‐reported outcome measures (PROMs) after ≥ 12 weeks of follow‐up were analysed. We used a linear mixed‐effects model to determine changes in scores during follow‐up. Results: Ninety‐five patients were included. Of these, 62 patients were using systemic immunosuppressants at baseline; the use of systemic immunosuppressants was continued during dupilumab treatment in 43 patients. From baseline to 16 weeks of treatment, the estimated mean Eczema Area and Severity Index score (0–72) decreased from 18·6 [95% confidence interval (CI) 16·0–21·4)] to 7·3 (95% CI 5·4–10·0), and the estimated mean PROMs showed a decrease of 41–66%. Investigator's Global Assessment 0 or 1 (clear/almost clear) was reached in 38% of the patients. Five patients discontinued dupilumab treatment due to side‐effects or ineffectiveness. Eye symptoms and orofacial (nonocular) herpes simplex virus (HSV) reactivation were reported in 62% and 8% of the patients, respectively. Conclusions: Dupilumab treatment in daily practice shows a clinically relevant improvement of physician‐reported outcome measures and PROMs, which is in line with efficacy data from clinical trials. Besides frequently reported eye symptoms and orofacial (nonocular) HSV reactivation, there were no apparent safety concerns. What's already known about this topic? Dupilumab has been shown to be an efficacious treatment for atopic dermatitis in several clinical trials. However, it is known that there may be considerable differences in patient characteristics and treatment responses between clinical trials and daily practice. What does this study add? This study presents the first experience with dupilumab treatment in 95 patients with atopic dermatitis in daily practice in two Dutch university hospitals. Less stringent inclusion and exclusion criteria and follow‐up schedules, in contrast to those used in clinical trials, might better represent daily practice. Dupilumab treatment shows a clinically relevant improvement of physician‐ and patient‐reported outcome measures; besides patient‐reported eye symptoms (in 59 of 95 patients; 62%) and an apparent increase in orofacial (nonocular) herpes simplex virus reactivation (eight of 95 patients; 8%), there were no other safety concerns during follow‐up up to 16 weeks of dupilumab treatment. Abstract : Linked Comment:  Deleuran and Vestergaard. Br J Dermatol 2020; 182 :275–276 . Plain language summary available online